المنهج التفاعلي: استثمار في نظرية الذكاءات المتعددة لجاردنر والمفهوم المتجدد للنص بالعصر الرقمي بزمن كورونا - بوطورة, حنان; منصوري, سميرة (جامعة الوادي - University of Eloued, 2021)
تركت جائحة كورونا انعكاسات كبيرة على قطاع التعليم، حيث أغلقت المدارس والجامعات وأصبحت نتيجة ذلك الحاجة للتعليم عن بعد ضرورة وحتمية وليس خيارا، كما صار تطوير المناهج التعليمية وفق معطيات العصر الرقمي ضرورة لا تتعلق فقط بالدول النامية والمتخلفة تكنولوجيا بل وأيضا الدول المتطورة التي توظف تكنولوجيا المعلومات في منظوماتها التربوية كوسيلة مساعدة في نقل المعارف للتلاميذ والطلاب، لأن هذا التعامل لم يكن كافيا لمواجهة تبعات جائحة كرورنا التي فرضت على العالم بأكمله أوضاعا جديدة لم يعهدها وطرحت اشكالية في مدى مرونة المناهج التعليمية القائمة على نظريات تربوية تتعامل مع تكنولوجيا المعلومات كوسيلة لنقل المعرفة وليست كقاعدة أساسية في بناء المناهج التعليمية، لذا نهدف من خلال هذه الورقة البحثية إلى اقتراح نموذج منهج تعليمي تفاعلي مرن يدمج معطيات العصر الرقمي المتمثلة في المعنى المتجدد للنص الرقمي ونظرية الذكاءات المتعددة لجاردنر. وعليه نطرح في هذه الورقة البحثية اشكالية استثمار المعنى المتجدد للنص بالعصر الرقمي ونظرية الذكاءات المتعددة لجاردنر لتطوير منهج تفاعلي قادر على مواجهة التحديات المختلفة لجائحة كورونا بالتعليم. The Corona pandemic has left significant repercussions on the education sector, as schools and universities are closed, and as a result the need for distance education has become a necessity and an inevitability and not an option, just as developing educational curricula according to the data of the digital age has become a necessity not only related to developing and underdeveloped countries, but also developed countries that employ information technology. In its educational systems as an aid in the transfer of knowledge to pupils and students , Because this dealings were not sufficient to face the consequences of the pandemic of our crises, which imposed on the whole world new conditions that it did not experience, and raised a problem in the extent of flexibility of educational curricula based on educational theories that deal with information technology as a means of transferring knowledge and not as a basic rule in building educational curricula, so we aim through This research paper proposes a flexible interactive educational curriculum model that integrates the digital age data represented by the renewed meaning of digital text and Gardner's theory of multiple intelligences. Therefore, in this research paper, we present the problem of investing the renewed meaning of the text in the digital age and Gardner's theory of multiple intelligences to develop an interactive approach capable of facing the various challenges of the Corona pandemic with education.
The interactive curriculum: An investment in Gardner's theory of multiple intelligences and the renewed concept of text in the digital age at the time of Corona
مقال
Keywords: عصر رقمي؛ نص متفرع؛ ذكاءات متعددة؛ منهج تعليمي؛ منهج تفاعلي.; Digital era, Branched text, Multiple intelligences, Educational curriculum, Interactive curriculum